HISTONE DEACETYLASE-1 is required for epigenome stability in Neurospora crassa - Felicia Ebot-Ojong; Aileen R. Ferraro; Rochelle E. Yap; Farh Kaddar; Clayton Hull-Crew; Ashley W. Scadden; Abigail M. Deaven; Andrew D. Klocko; Zachary A. Lewis (Proceedings of the National Academy of Sciences, 2025)
Polycomb group (PcG) proteins form chromatin modifying complexes that stably repress lineage- or context-specific genes in animals, plants, and some fungi. Polycomb Repressive Complex 2 (PRC2) catalyzes trimethylation of lysine 27 on histone H3 (H3K27me3) to assemble repressive chromatin. In the model fungus Neurospora crassa, H3K27me3 deposition is regulated by the H3K36 methyltransferase ASH1 and components of constitutive heterochromatin including the H3K9me3-binding protein HETEROCHROMATIN PROTEIN 1 (HP1). Hypoacetylated histones are a defining feature of both constitutive heterochromatin and PcG-repressed chromatin, but how histone deacetylases (HDACs) contribute to normal H3K27me3 and transcriptional repression within PcG-repressed chromatin is poorly understood. We performed a genetic screen to identify HDACs required for repression of PRC2-methylated genes. In the absence of HISTONE DEACETYLASE-1 (HDA-1), PRC2-methylated genes were activated and H3K27me3 was depleted from typical PRC2-targeted regions. At constitutive heterochromatin, HDA-1 deficient cells displayed reduced H3K9me3, hyperacetylation, and aberrant enrichment of H3K27me3 and H3K36me3. CHROMODOMAIN PROTEIN-2 (CDP-2) is required to target HDA-1 to constitutive heterochromatin and is also required for normal H3K27me3 patterns. Patterns of aberrant H3K27me3 were distinct in isogenic ∆ hda-1 strains, suggesting that loss of HDA-1 causes stochastic or progressive epigenome dysfunction. To test this, we constructed a new Δhda-1 strain and performed a laboratory “aging” experiment. Deletion of hda-1 led to progressive epigenome decay over hundreds of nuclear divisions. Together, our data indicate that HDA-1 is a critical regulator of epigenome stability in N. crassa.